Cathode materials and methods

By adjusting the content and distribution of magnesium and cobalt in lithium nickel oxide materials, especially increasing the cobalt enrichment layer through surface modification, the problem of insufficient capacity retention in lithium secondary battery packs is solved, and high capacity retention is achieved and low DC internal resistance battery performance.

CN119137071APending Publication Date: 2024-12-13EV METALS UK LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202180027965.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-03-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When the existing lithium transition metal oxide material is used as a cathode material in a lithium secondary battery pack, the capacity retention rate is insufficient, making it difficult to maintain battery life during a large number of charging cycles.

Method used

Using surface-modified granular lithium nickel oxide materials containing magnesium and cobalt, the capacity retention rate is improved by adjusting the content of magnesium and cobalt and their distribution. The specific method includes mixing the lithium, nickel, cobalt and magnesium compounds and calcining them, and increasing the cobalt enrichment layer through the surface modification step to ensure that the cobalt content of the surface layer reaches or exceeds 0.8% of the total weight to improve the material. Cyclic performance.

Benefits of technology

The capacity retention rate of the lithium secondary battery pack is significantly improved, ensuring that the capacity retention rate reaches 94% or more after 50 cycles, and reducing the increase in DC internal resistance and extending the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003885787010000301
    Figure BDA0003885787010000301
  • Figure BDA0003885787010000331
    Figure BDA0003885787010000331
  • Figure BDA0003885787010000341
    Figure BDA0003885787010000341
Patent Text Reader

Abstract

The present invention relates to improved particulate lithium nickel oxide materials useful as cathode materials in lithium secondary batteries. Also provided are methods for preparing such lithium nickel oxide materials, as well as electrodes and batteries comprising the materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to improved particulate lithium nickel oxide materials useful as cathode materials in lithium secondary batteries. The present invention also provides methods for preparing such lithium nickel oxide materials, as well as electrodes and batteries comprising the materials. Background Art

[0002] Lithium transition metal oxide materials having the formula LiMO2, where M typically comprises one or more transition metals, are useful as cathode materials in lithium-ion batteries. Examples include LiNiO2 and LiCoO2.

[0003] US 6921609 B2 describes a composition suitable for use as a cathode material for lithium batteries, the composition comprising a composition having the empirical formula Li x M' z Ni 1-y M” y A core composition of O2 and a coating on the core having a greater Co to Ni ratio than the core.

[0004] WO 2013 / 025328 A1 describes particles comprising a plurality of crystallites comprising a first composition having a layered α-NaFeO2 type structure. The particles comprise grain boundaries between adjacent crystallites, and the cobalt concentration in the grain boundaries is greater than the cobalt concentration in the crystallites. Cobalt enrichment is achieved by treating the particles with a solution of LiNO3 and Co(NO3)2, followed by spray drying and calcining.

[0005] As demand for lithium-ion battery packs for high-end applications such as electric vehicles (EVs) increases, it is imperative to use cathode materials that not only provide an acceptable specific capacity, but also maintain that capacity extremely well over a large number of charge cycles so that the range per charge remains as consistent as possible over the life of the vehicle. Capacity retention is often also referred to as the "cycling performance" of the battery pack.

[0006] Therefore, there is still a need for improved lithium transition metal oxide materials and methods for making them. In particular, there is still a need to improve the capacity retention of lithium transition metal oxide materials when used as cathode materials in lithium secondary batteries. Summary of the invention

[0007] The present inventors have discovered that the presence of both magnesium and cobalt in particulate lithium nickel oxide cathode materials can improve their capacity retention. As shown in the following examples, the capacity retention is strongly dependent on the magnesium content, but increasing the magnesium content to too high a level can have a deleterious effect on the specific capacity. Similarly, the examples show that increasing the cobalt content also improves the capacity retention, but the capacity retention is more strongly dependent on the cobalt content in the enriched layer on the surface of the particles, rather than the cobalt content in the core. In addition, there is no correlation between increasing the cobalt content in the surface layer of the material and the reduction in capacity. Therefore, it is very advantageous to provide a material with an increased cobalt content in the surface enriched layer (thereby optionally reducing the magnesium and / or core cobalt content).

[0008] Thus, a first aspect of the present invention is a surface modified particulate lithium nickel oxide material comprising particles having formula I

[0009] Li a Ni x Co y Mg z Al p M q O 2+b

[0010] Formula I

[0011] in:

[0012] 0.8≤a≤1.2

[0013] 0.8≤x<1

[0014] 0.010≤y≤0.12

[0015] 0.007≤z≤0.030

[0016] 0≤p≤0.01

[0017] 0≤q≤0.2; and

[0018] -0.2≤b≤0.2;

[0019] wherein M is selected from the group consisting of Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, W, Mo, Ta, Y, Sc, Nb, Pb, Ru, Rh and Zn and combinations thereof; and

[0020] wherein the particle comprises a core and an enriched surface layer at a surface of the core, and wherein the enriched surface layer comprises 0.8 wt % or more of cobalt based on the total weight of the particle.

[0021] A second aspect of the present invention is a method for preparing a granular lithium nickel oxide material having formula I

[0022] Li a Ni x Co y Mg z Al p M q O 2+b

[0023] Formula I

[0024] in:

[0025] 0.8≤a≤1.2

[0026] 0.8≤x<1

[0027] 0.010≤y≤0.12

[0028] 0.010≤z≤0.030

[0029] 0≤p≤0.01

[0030] 0≤q≤0.2; and

[0031] -0.2≤b≤0.2;

[0032] wherein M is selected from the group consisting of Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, W, Mo, Ta, Y, Sc, Nb, Pb, Ru, Rh and Zn and combinations thereof; and

[0033] The method comprises the following steps:

[0034] mixing a lithium-containing compound with a nickel-containing compound, a cobalt-containing compound, a magnesium-containing compound, and optionally an M-containing compound and / or an aluminum-containing compound to obtain a mixture, wherein a single compound may optionally contain two or more of Ni, Co, Mg, Al and M;

[0035] calcining the mixture to obtain a calcined material; and

[0036] The first calcined material is contacted with a cobalt-containing compound and optionally one or more of an aluminum-containing compound, a lithium-containing compound, and an M-containing compound in a surface modification step to form an enriched surface layer on the first calcined material, such that the enriched surface layer contains 0.8 wt% or more of cobalt based on the total weight of the particle.

[0037] A third aspect of the present invention provides a particulate lithium nickel oxide obtained or obtainable by the method described herein.

[0038] A fourth aspect of the present invention provides a cathode material for a lithium secondary battery pack, the cathode material comprising the particulate lithium nickel oxide material according to the first aspect.

[0039] A fifth aspect of the present invention provides a cathode comprising the particulate lithium nickel oxide material according to the first aspect.

[0040] The sixth aspect of the present invention provides a lithium secondary battery or battery pack (eg, a secondary lithium ion battery pack) comprising the cathode according to the fifth aspect. The battery pack generally further comprises an anode and an electrolyte.

[0041] A seventh aspect of the present invention provides use of the particulate lithium nickel oxide according to the first aspect for preparing a cathode of a secondary lithium battery (eg, a secondary lithium ion battery).

[0042] An eighth aspect of the present invention provides use of the particulate lithium nickel oxide according to the first aspect as a cathode material to improve the capacity retention or cycle performance of a lithium secondary battery or battery pack.

[0043] The ninth aspect is a method for improving the capacity retention or cycle performance of a lithium secondary battery or battery pack, the method comprising using a cathode material in the battery or battery pack, wherein the cathode material comprises the particulate lithium nickel oxide material according to the first aspect. DETAILED DESCRIPTION

[0044] The preferred and / or optional features of the present invention will now be described. Unless the context otherwise requires, any aspect of the present invention can be combined with any other aspect of the present invention. Unless the context otherwise requires, any of the preferred and / or optional features of any aspect can be combined with any aspect of the present invention in a separate or combined manner. It is desirable that the upper and lower limits of the scope can be combined independently, and the various ranges and values ​​provided for a, b, x, y, z, p and q can be combined with each other and with other feature combinations described herein.

[0045] The particulate lithium nickel oxide material has a composition according to Formula I defined above. The compositions described herein can be determined by inductively coupled plasma (ICP) analysis as described below in the Examples section. It may be preferred that the compositions described herein are ICP compositions. Similarly, the weight % content of the elements in the particulate lithium nickel oxide material can be determined using ICP analysis. The weight % values ​​described herein are determined by ICP and are with respect to the total weight of the particles analyzed (except for the weight % lithium carbonate defined separately below).

[0046] In Formula I, 0.8≤a≤1.2. In some embodiments, a is greater than or equal to 0.9, 0.95, 0.99, or 1.0. In some embodiments, a is less than or equal to 1.1, or less than or equal to 1.05. In some embodiments, 0.90≤a≤1.10, for example, 0.95≤a≤1.05. In some embodiments, 0.99≤a≤1.05 or 1.0≤a≤1.05. 0.95≤a≤1.05 may be particularly preferred.

[0047] In Formula I, 0.8≤x<1. In some embodiments, 0.85≤x<1 or 0.9≤x<1. In some embodiments, x is less than or equal to 0.99, 0.98, 0.97, 0.96, or 0.95. In some embodiments, x is greater than or equal to 0.85, 0.9, or 0.95. In some embodiments, 0.8≤x≤0.99, such as 0.85≤x≤0.98, 0.85≤x≤0.98, 0.85≤x≤0.97, 0.85≤x≤0.96, or 0.90≤x≤0.95. 0.85≤x≤0.98 may be particularly preferred.

[0048] In Formula I, 0.010≤y≤0.12. In some embodiments, y is greater than or equal to 0.03, 0.05, 0.055, or 0.06. Including at least this amount of cobalt in the entire composition provides excellent capacity retention. In some embodiments, y is less than or equal to 0.10, 0.095, 0.093, 0.090, or 0.085. In some embodiments, 0.03≤y≤0.095. According to the present invention, by transferring the cobalt content to the enriched surface layer, excellent capacity retention can be obtained while minimizing the total cobalt content. In some embodiments, 0.05≤y≤0.0.09. In some embodiments, 0.055≤y≤0.085.

[0049] In Formula I, 0.007≤z≤0.030. In some embodiments, z is greater than or equal to 0.008, 0.009, 0.010, 0.012, 0.015, 0.018, 0.020, or 0.022. At least this level of magnesium content can provide improved capacity retention. In some embodiments, z is less than or equal to 0.029, 0.028, 0.027, 0.025, 0.022, or 0.020. Avoiding excessive magnesium content may be advantageous because it may result in a higher specific capacity. In the case of a cobalt content in the surface enriched layer as provided by the present invention, excellent capacity retention can be obtained even at relatively low magnesium contents.

[0050] In Formula I, 0.004≤p≤0.01. In some embodiments, p is less than or equal to 0.0090, 0.0080, 0.0075, or 0.0070. In some embodiments, p is greater than or equal to 0.005, 0.0055, or 0.0060. In some embodiments, 0.004≤p≤0.0090, 0.005≤p≤0.008, 0.0055≤p≤0.0075, or 0.006≤p≤0.007. 0.0055≤p≤0.0075 or 0.0055≤p≤0.0080 may be particularly preferred.

[0051] In Formula I, -0.2≤b≤0.2. In some embodiments, b is greater than or equal to -0.1. In some embodiments, b is less than or equal to 0.1. In some embodiments, -0.1≤b≤0.1. In some embodiments, b is 0 or about 0. In some embodiments, b is 0.

[0052] In Formula I, M is one or more selected from Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, W, Mo, Ta, Y, Sc, Nb, Pb, Ru, Rh, and Zn. In some embodiments, M is one or more selected from Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, and Zn. In some embodiments, M is Mn. In some embodiments, M represents a dopant that is present in the core of the particle but not in the enriched surface layer.

[0053] In Formula I, 0≤q≤0.2. In some embodiments, 0≤q≤0.15. In some embodiments, 0≤q≤0.10. In some embodiments, 0≤q≤0.05. In some embodiments, 0≤q≤0.04. In some embodiments, 0≤q≤0.03. In some embodiments, 0≤q≤0.02. In some embodiments, 0≤q≤0.01. In some embodiments, q is 0.

[0054] In some embodiments:

[0055] 0.95≤a≤1.05

[0056] 0.85≤x<1

[0057] 0.010≤y≤0.10

[0058] 0.012≤z≤0.030

[0059] 0.0055≤p≤0.0080

[0060] 0≤q≤0.2, and

[0061] -0.2≤b≤0.2;

[0062] Wherein M is selected from Al, Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, W, Mo, Ta, Y, Sc, Nb, Pb, Ru, Rh and Zn and combinations thereof.

[0063] In some embodiments:

[0064] 0.95≤a≤1.05

[0065] 0.85≤x<1

[0066] 0.010≤y≤0.10

[0067] 0.012≤z≤0.030

[0068] 0.0055≤p≤0.0080

[0069] q = 0; and

[0070] b=0.

[0071] In some embodiments:

[0072] 0.95≤a≤1.05

[0073] 0.85≤x<1

[0074] 0.010≤y≤0.093

[0075] 0.012≤z≤0.030

[0076] 0.0055≤p≤0.0080

[0077] q = 0; and

[0078] b=0.

[0079] In some embodiments:

[0080] 0.95≤a≤1.05

[0081] 0.85≤x<1

[0082] 0.010≤y≤0.085

[0083] 0.012≤z≤0.025

[0084] 0.0055≤p≤0.0080

[0085] q = 0; and

[0086] b=0.

[0087] In some embodiments:

[0088] 0.95≤a≤1.05

[0089] 0.85≤x<1

[0090] 0.055≤y≤0.085

[0091] 0.012≤z≤0.025

[0092] 0.0055≤p≤0.0080

[0093] q = 0; and

[0094] b=0.

[0095] In some embodiments:

[0096] 0.95≤a≤1.05

[0097] 0.85≤x<1

[0098] 0.010≤y≤0.030

[0099] 0.012≤z≤0.025

[0100] 0.0055≤p≤0.0080

[0101] q = 0; and

[0102] b=0.

[0103] In some embodiments, the particulate lithium nickel oxide material is a crystalline (or substantially crystalline) material. It may have an α-NaFeO2 type structure. It may be a polycrystalline material, meaning that each particle of the lithium nickel oxide material is composed of a plurality of crystallites (also referred to as grains or primary particles) that are agglomerated together. The grains are typically separated by grain boundaries. In the case where the particulate lithium nickel oxide is polycrystalline, it is understood that the particles comprising polycrystalline lithium nickel oxide are secondary particles.

[0104] The granular lithium nickel oxide material of formula I comprises an enriched surface, i.e., comprises a core material that has been surface-modified (subjected to a surface modification method) to form an enriched surface layer. In some embodiments, the surface modification is produced by contacting the core material with a cobalt-containing compound and one or more other metal-containing compounds, and then optionally calcining the material. The compound can be in solution, and in this context herein, the term "compound" refers to the corresponding dissolved substance. For clarity, the discussion of the composition according to formula I herein in the context of surface-modified particles relates to the entire particle, i.e., the particle including the enriched surface layer.

[0105] As used herein, the terms "surface modified," "enriched surface," and "enriched surface layer" refer to a particulate material comprising a core material that has been subjected to a surface modification or surface enrichment process to increase the concentration of cobalt at or near the surface of the particle. Thus, the term "enriched surface layer" refers to a layer of material at or near the surface of a particle that contains a higher concentration of cobalt than the remainder of the material of the particle (i.e., the core of the particle).

[0106] In some embodiments, the particle comprises a higher concentration of Al in the enriched surface layer than in the core. In some embodiments, all or substantially all of the Al in the particle is in the enriched surface layer. In some embodiments, the core contains no Al or substantially no Al, e.g., less than 0.01 wt % Al based on the total particle weight.

[0107] As used herein, the content of a given element in the surface enriched layer is calculated by determining the weight percent of the element in the particulate lithium nickel oxide material before surface enrichment (sometimes referred to herein as the first calcined material or core material) by ICP, obtaining a value A, determining the weight percent of the element in the final particulate lithium nickel oxide material after surface enrichment (and optionally further calcination) by ICP, obtaining a value B, and subtracting value A from value B. Similarly, the content of a given element in the core can be determined by determining the weight percent of the element in the particulate lithium nickel oxide material before surface enrichment (sometimes referred to herein as the first calcined material or core material) by ICP.

[0108] As the technician will understand, during the preparation, storage or use of the material, the element can migrate between the core and the surface layer. In this article, when an element is stated to be present in the core (or not present in the core, or present in the core with a certain amount), this should be understood to refer to the element that is intentionally added to the core (or excluded from the core, or added to the core with a certain amount), and it is not intended to exclude it from the scope of the protective material when the distribution of the element is changed by migration during preparation, storage or use. Similarly, when an element is stated to be present in the surface enrichment layer (or not present in the surface enrichment layer, or present in the surface enrichment layer with a certain amount), this should be understood to refer to the element that is intentionally added to the surface enrichment layer (or excluded from the surface enrichment layer, or added to the surface enrichment layer with a certain amount), and it is not intended to exclude it from the scope of the protective material when the distribution of the element is changed by migration during preparation, storage or use. For example, when the surface enrichment layer contains 0.8 wt% cobalt, this means that 0.8 wt% cobalt is added in the surface enrichment step, but it does not exclude that some of the Co added in the surface enrichment step has migrated to the material of the core.

[0109] In some embodiments, the surface enriched layer comprises Co and optionally one or more of Li and Al. In some embodiments, the surface enriched layer comprises Co, Al, and optionally Li. In some embodiments, the surface enriched layer comprises Co, Al, and Li. In some embodiments, the enriched surface layer does not contain any magnesium or nickel, for example, contains less than about 0.01% by weight of each of magnesium and nickel. In some embodiments, the enriched surface layer contains cobalt and optionally aluminum and / or lithium, but does not contain any magnesium or nickel, for example, contains less than about 0.01% by weight of each of magnesium and nickel.

[0110] In some embodiments, all or substantially all of the magnesium is in the core of the particle.In some embodiments, the enriched surface layer is free or substantially free of magnesium, such as less than 0.01 wt % Mg based on total particle weight.

[0111] In the material of the present invention, the enriched surface layer comprises 0.8 wt % or more cobalt based on the total weight of the particle. In some embodiments, the surface enriched layer comprises greater than or equal to 1.0, 1.1, 1.2, 1.3, 1.5, 1.8 or 2.0 wt % cobalt. In some embodiments, the surface enriched layer comprises less than or equal to 3, 2.8, 2.7, 2.5, 2.3 or 2.0 wt % cobalt. The cobalt content in the surface enriched layer is calculated as described above.

[0112] In the material of the invention, the core of the material may for example contain 0.5 wt% cobalt or more. It may contain 1 or 1.5 wt% or more. It may contain 5 wt% or less, for example 4.5, 4, 3.5 or 3 wt% or less.

[0113] In some embodiments, the ratio of the mass of material in the enriched surface layer to the mass of material in the core is from 0.01 to 0.04, eg, from 0.01 to 0.03, from 0.01 to 0.025, or from 0.014 to 0.022.

[0114] The granular lithium nickel oxide material typically has a D50 particle size of at least 4 μm, for example, at least 5 μm, at least 5.5 μm, at least 6.0 μm, or at least 6.5 μm. The particles (e.g., secondary particles) of lithium nickel oxide typically have a D50 particle size of 20 μm or less, for example, 15 μm or less or 12 μm or less. In some embodiments, the D50 particle size is from about 5 μm to about 20 μm, for example, from about 5 μm to about 19 μm, for example, from about 5 μm to about 18 μm, for example, from about 5 μm to about 17 μm, for example, from about 5 μm to about 16 μm, for example, from about 5 μm to about 15 μm, for example, from about 5 μm to about 12 μm, for example, from about 5.5 μm to about 12 μm, for example, from about 6 μm to about 12 μm, for example, from about 6.5 μm to about 12 μm, for example, from about 7 μm to about 12 μm, for example, from about 7.5 μm to about 12 μm. Unless otherwise specified herein, D50 particle size refers to Dv50 (volume median diameter) and can be determined by using the method set forth in 2017 ASTM B822 under the Mie scattering approximation, for example, using a Malvern Mastersizer 3000.

[0115] In some embodiments, the D10 particle size of the material is about 0.1 μm to about 10 μm, such as about 1 μm to about 10 μm, about 2 μm to about 8 μm, or about 5 μm to about 7 μm. Unless otherwise specified herein, the D10 particle size refers to Dv10 (10% intercept in the cumulative volume distribution) and can be determined by using the method shown in 2017 ASTM B822 under the Mie scattering approximation, such as using a Malvern Mastersizer 3000.

[0116] In some embodiments, the D90 particle size of the material is about 10 μm to about 40 μm, such as about 12 μm to about 35 μm, about 12 μm to about 30 μm, about 15 μm to about 25 μm, or about 16 μm to about 20 μm. Unless otherwise specified herein, the D90 particle size refers to the Dv90 (90% intercept in the cumulative volume distribution) and can be determined by using the method shown in 2017 ASTM B822 under the Mie scattering approximation, for example, using a Malvern Mastersizer 3000.

[0117] In some embodiments, the tap density of the particulate lithium nickel oxide is about 1.9 g / cm 3 To about 2.8g / cm 3 , for example about 1.9 g / cm 3 To about 2.4g / cm 3 .

[0118] The tap density of the material can be measured appropriately by loading 25 mL of powder into a graduated cylinder. Record the mass of the powder. Transfer the loaded graduated cylinder to a Copley Tap Density Tester JV Series. Tap the material 2000 times and remeasure the volume. Divide the remeasured volume by the mass of the material to record the tap density.

[0119] The particulate lithium nickel oxide typically contains less than 1.5 wt % surface Li2CO3. It may contain less than 1.4 wt %, for example, less than 1.3 wt %, less than 1.2 wt %, less than 1.1 wt %, less than 1.0 wt %, less than 0.9 wt %, less than 0.8 wt %, less than 0.7 wt %, or less than 0.6 wt % surface Li2CO3. It may have 0 wt % surface Li2CO3, but in some embodiments, may be at least 0.01 wt %, 0.02 wt %, or 0.04 wt % surface Li2CO3.

[0120] The amount of surface Li2CO3 can be determined by titration with HCl using bromophenol blue indicator. Typically, the first titration step is performed with HCl and phenolphthalein indicator, followed by titration with bromophenol blue indicator to remove any lithium hydroxide. The titration protocol may include the following steps:

[0121] - extracting surface lithium carbonate from a sample of particulate lithium nickel oxide material by stirring in deionized water for 5 minutes to provide an extract solution, and separating the extract solution from residual solids;

[0122] - Add phenolphthalein indicator to the extract solution and titrate with HCl solution until the extract solution becomes clear (which indicates that all LiOH has been removed);

[0123] - Add bromophenol blue indicator to the extract solution and titrate with HCl solution until the extract solution turns yellow; (the amount of lithium carbonate in the extract solution can be calculated from this titration step); and

[0124] - Calculate the weight % of surface lithium carbonate in the particulate lithium nickel oxide material sample assuming 100% extraction of the surface lithium carbonate into the extract solution.

[0125] The particulate lithium nickel oxide of the present invention is characterized by improved capacity retention for cells incorporated as cathode materials, especially high capacity retention after 50 cycles. When measured in a half-cell button cell relative lithium battery at a temperature of 23°C, a charge / discharge rate of 1C and a voltage window of 3.0-4.3V, the electrode loading is 9.0 mg / cm 2 , the electrode density is 3.0g / cm 3It has been found that materials according to the present invention can provide a capacity retention of greater than 94%, and in some cases up to about 98%, after 50 cycles. The capacity retention percentage after 50 cycles is defined as the capacity of the battery after the 50th cycle divided by the initial capacity of the battery after the first charge. For clarity, one cycle includes one complete charge and discharge of the battery. For example, a capacity retention of 90% means that the capacity of the battery after the 50th cycle is 90% of the initial capacity.

[0126] One aspect of the invention is a lithium secondary cell or battery wherein the cell or battery has a capacity retention of at least 93% after 50 cycles at 23°C and 1C charge / discharge rate and a voltage window of 3.0-4.3V.

[0127] The material can have a capacity retention of at least 93% (after 50 cycles in a half-cell coin cell to lithium battery at 9.0 mg / cm 2 The electrode loading is 3.0 g / cm 3 The electrode density was tested at 23 °C and 1C charge / discharge rate and a voltage window of 3.0-4.3 V).

[0128] In some embodiments, the capacity retention is at least 94%, such as at least 95%, such as at least 96%, such as at least 97%.

[0129] The materials of the present invention are also characterized by unexpectedly low direct current internal resistance (DCIR). As the secondary cell or battery is cycled, the DCIR tends to increase over time. It has been found that when the cell is at a temperature of 23°C, in a half-cell button cell to lithium battery, at a charge / discharge rate of 1C and a voltage window of 3.0-4.3V, and 9.0mg / cm 2 The electrode loading is 3.0 g / cm 3 When tested at an electrode density of 1000 mg / cm2, materials according to the present invention provide a DCIR increase of less than 50% after 50 cycles, and in some cases the increase is as low as 24%. The material can have a DCIR increase of less than 50% (after 50 cycles, in a half-cell button cell to a lithium battery, at 9.0 mg / cm2). 2 The electrode loading is 3.0 g / cm 3 The electrode density was tested at 23 °C and 1C charge / discharge rate and a voltage window of 3.0-4.3 V).

[0130] In some embodiments, the percent increase in DCIR is less than 45%, such as less than 40%, such as less than 35%, such as less than 30%, such as less than 25%.

[0131] The materials of the present invention are also characterized by high specific capacity. It has been found that when in a battery, in a half-cell coin cell for lithium metal batteries, at 23°C, 1C discharge rate and a voltage window of 3.0-4.3V, and 9.0mg / cm 2 The electrode loading is 3.0 g / cm 3 When tested at an electrode density of 1000 mAh / g, the material according to the present invention provides a specific capacity of at least 160 mAh / g, in some cases up to 190 mAh / g. This high specific capacity combined with high capacity retention during cycling provides a cell or battery with improved performance and extended service life, which is useful in high-performance applications such as electric vehicles.

[0132] When in the battery, in a half-cell coin cell for lithium metal batteries, at 23 °C, 1C discharge rate and a voltage window of 3.0-4.3 V, and 9.0 mg / cm 2 The electrode loading is 3.0 g / cm 3 When tested at an electrode density of , the material can have a specific capacity of at least 180 mAh / g. In some embodiments, the specific capacity is at least 190 mAh / g, such as at least 200 mAh / g.

[0133] The method for preparing particulate lithium nickel oxide generally comprises the following steps:

[0134] mixing a lithium-containing compound with a nickel-containing compound, a cobalt-containing compound, a magnesium-containing compound, and optionally an M-containing compound and / or an aluminum-containing compound to obtain a mixture, wherein a single compound may optionally contain two or more of Ni, Co, Mg, Al and M;

[0135] calcining the mixture to obtain a first calcined material; and

[0136] contacting the first calcined material with an aluminum-containing compound and optionally one or more of a cobalt-containing compound, a lithium-containing compound, and an M-containing compound in a surface modification step to form an enriched surface layer on the first calcined material;

[0137] Wherein M is selected from Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, W, Mo, Ta, Y, Sc, Nb, Pb, Ru, Rh and Zn and combinations thereof.

[0138] In some embodiments, the first calcined material is a core material having Formula II:

[0139] Li a1 Ni x1 Co y1 Mg z1 Al p1 Mq1 O 2+b1

[0140] Formula II

[0141] in:

[0142] 0.8≤a1≤1.2

[0143] 0.8≤x1<1

[0144] 0.010≤y1≤0.12

[0145] 0.007≤z1≤0.030

[0146] 0≤p1≤0.01

[0147] 0≤q1≤0.2; and

[0148] -0.2≤b1≤0.2;

[0149] Wherein M is selected from Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, W, Mo, Ta, Y, Sc, Nb, Pb, Ru, Rh and Zn and combinations thereof.

[0150] In some embodiments, p1 = 0, such that the core material has the formula:

[0151] Li a1 Ni x1 Co y1 Mg z1 M q1 O 2+b1

[0152] In some embodiments, the method comprises a further calcination step after the surface modification step.

[0153] In some embodiments, q1=0.

[0154] The lithium-containing compound may be selected from lithium hydroxide (eg, LiOH or LiOH.H2O), lithium carbonate (Li2CO3), and hydrated forms thereof. Lithium hydroxide may be particularly preferred.

[0155] The nickel-containing compound may be selected from nickel hydroxide (Ni(OH)2), nickel oxide (NiO), nickel oxyhydroxide (NiOOH), nickel sulfate, nickel nitrate, nickel acetate, and hydrated forms thereof. Nickel hydroxide may be particularly preferred.

[0156] The cobalt-containing compound may be selected from cobalt hydroxide (Co(OH)2), cobalt oxide (CoO, Co2O3, Co3O4), cobalt oxyhydroxide (CoOOH), cobalt sulfate, cobalt nitrate, cobalt acetate, and hydrated forms thereof. Cobalt hydroxide may be particularly preferred.

[0157] The magnesium-containing compound may be selected from magnesium hydroxide (Mg(OH)2), magnesium oxide (MgO), magnesium sulfate, magnesium nitrate, magnesium acetate and hydrated forms thereof. Magnesium hydroxide may be particularly preferred.

[0158] The M-containing compound may be selected from the group consisting of a hydroxide of M, an oxide of M, a nitrate of M, a sulfate of M, a carbonate of M or an acetate of M and hydrated forms thereof. The hydroxide of M may be particularly preferred.

[0159] Alternatively, two or more of nickel, cobalt, magnesium and optionally M may be provided as a mixed metal hydroxide, such as a mixed nickel cobalt hydroxide or a mixed nickel cobalt M hydroxide. The mixed metal hydroxide may be a coprecipitated hydroxide. It may be polycrystalline.

[0160] The mixed metal hydroxide may have a composition according to Formula III:

[0161] Ni x Co y Mg z M q (OH) 2+b

[0162] Formula III

[0163] wherein x, y, z, q and b are each independently as defined herein. If a cobalt enrichment step is performed (as described below), it may be preferred that the value of y in Formula III is less than the value of y in Formula I.

[0164] Such mixed metal hydroxides can be prepared by coprecipitation methods well known to those skilled in the art. These methods may involve, for example, coprecipitating the mixed metal hydroxide from a solution of a metal salt such as a metal sulfate in the presence of ammonia and a base such as NaOH. In some cases, suitable mixed metal hydroxides may be obtained from commercial suppliers known to those skilled in the art.

[0165] The calcining step may be carried out at a temperature of at least 400°C, at least 500°C, at least 600°C, or at least 650°C. The calcining step may be carried out at a temperature of 1000°C or less, 900°C or less, 800°C or less, or 750°C or less. The material to be calcined may be maintained at a temperature of 400°C, at least 500°C, at least 600°C, or at least 650°C for a period of at least 2 hours, at least 5 hours, at least 7 hours, or at least 10 hours. The time period may be less than 24 hours.

[0166] The calcining step can be carried out in a CO2-free atmosphere. For example, during calcination and optionally during cooling, CO2-free air can flow through the material to be calcined. For example, CO2-free air can be a mixture of oxygen and nitrogen. The CO2-free atmosphere can be oxygen (e.g., pure oxygen). Preferably, the atmosphere is an oxidizing atmosphere. As used herein, the term "CO2-free" is intended to include an atmosphere containing less than 100 ppm CO2, such as less than 50 ppm CO2, less than 20 ppm CO2, or less than 10 ppm CO2. These CO2 levels can be achieved by removing CO2 using a CO2 scrubber.

[0167] In some embodiments, the CO2-free atmosphere comprises a mixture of O2 and N2. In some embodiments, the mixture comprises a greater amount of N2 than O2. In some embodiments, the mixture comprises N2 and O2 in a ratio of 50:50 to 90:10, such as 60:40 to 90:10, such as about 80:20.

[0168] In some embodiments, the particulate lithium nickel oxide material of Formula I comprises a surface-modified structure comprising a core and an enriched surface layer at the surface of the core, resulting from a surface modification step of a core material having Formula II:

[0169] Li a1 Ni x1 Co y1 Mg z1 Al p1 M q1 O 2+b1

[0170] Formula II

[0171] in:

[0172] 0.8≤a1≤1.2

[0173] 0.8≤x1<1

[0174] 0.010≤y1≤0.12

[0175] 0.007≤z1≤0.030

[0176] 0≤p1≤0.01

[0177] 0≤q1≤0.2; and

[0178] -0.2≤b1≤0.2;

[0179] Wherein M is selected from Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, W, Mo, Ta, Y, Sc, Nb, Pb, Ru, Rh and Zn and combinations thereof.

[0180] The surface modification step may comprise contacting the core material with one or more of an aluminum-containing compound and optionally a cobalt-containing compound, a lithium-containing compound and an M-containing compound. The aluminum-containing compound and optionally a cobalt-containing compound, a lithium-containing compound and an M-containing compound may be provided in solution, for example in an aqueous solution.

[0181] In some embodiments, p1 = 0, such that the core material has the formula:

[0182] Li a1 Ni x1 Co y1 Mg z1 M q1 O 2+b1

[0183] In some embodiments, q1=0.

[0184] The surface modification step (also referred to herein as the surface enrichment step) of the method of the present invention includes contacting the core material with cobalt to increase the concentration of cobalt in the grain boundaries of the particles and / or at or near the surface of the particles. In some embodiments, the surface modification step (also referred to herein as the surface enrichment step) includes contacting the core material with another metal (selected from one or more of aluminum, lithium and M) to increase the concentration of this metal in the grain boundaries of the particles and / or at or near the surface of the particles. Surface modification can be carried out by contacting the core material with a cobalt-containing compound and optionally one or more other metal-containing compounds. For example, the compound can be independently selected from nitrates, sulfates or acetates. Nitrates may be particularly preferred. The compound can be provided in the form of a solution (e.g., an aqueous solution). The compound is soluble in water.

[0185] The mixture of the core material and the cobalt-containing compound and optionally one or more other metal-containing compounds may be heated to a temperature of, for example, at least 40° C., such as at least 50° C. The temperature may be below 100° C. or below 80° C. When the cobalt-containing compound and optionally one or more other metal-containing compounds are provided in solution, the mixture of solution and intermediate may be dried (e.g. by evaporating the solvent or by spray drying).

[0186] The cobalt-containing compound and optionally one or more other metal-containing compounds may be provided as a composition, referred to herein as a "surface modification composition." The surface modification composition may include a solution (eg, an aqueous solution) of the cobalt-containing compound and optionally one or more other metal-containing compounds.

[0187] The surface modification composition may comprise a cobalt-containing compound and optionally one or more of a lithium-containing compound, an aluminum-containing compound, and an M-containing compound. The surface modification composition may comprise a cobalt-containing compound and optionally one or more of a lithium-containing compound and an aluminum-containing compound. The surface modification composition may comprise a cobalt-containing compound, an aluminum-containing compound, and optionally a lithium-containing compound. The surface modification composition may comprise a cobalt-containing compound as the only metal-containing compound (i.e., thus lacking a lithium-containing compound, an aluminum-containing compound, and an M-containing compound).

[0188] The cobalt-containing compound, aluminum-containing compound, lithium-containing compound and M-containing compound used in the surface modification step may be defined as above with reference to the cobalt-containing compound, aluminum-containing compound, lithium-containing compound and M-containing compound used in the formation of the intermediate (core) material. It may be particularly preferred that each of the cobalt-containing compound and one or more other metal-containing compounds is a metal-containing nitrate. It may be particularly preferred that the aluminum-containing compound is aluminum nitrate. It may be particularly preferred that the lithium-containing compound is lithium nitrate. It may be particularly preferred that the cobalt-containing compound is cobalt nitrate. It may be preferred that the cobalt-containing compound, the aluminum-containing compound and the lithium-containing compound are soluble in water.

[0189] In some embodiments, the surface modification step includes contacting the core material with another metal-containing compound in an aqueous solution. The core material can be added to the aqueous solution to form a slurry or suspension. In some embodiments, the slurry is stirred or agitated. In some embodiments, after the core material is added to the aqueous solution, the weight ratio of the core material to water in the slurry is about 1.5:1 to about 1:1.5, such as about 1.4:1 to about 1:1.4, about 1.3:1 to about 1:1.3, about 1.2:1 to about 1:1.2 or about 1.1:1 to about 1:1.1. The weight ratio can be about 1:1.

[0190] Typically, the surface modification step is performed after the first calcination step described above.

[0191] The surface modification step may be followed by a second calcination step. The second calcination step may be carried out at a temperature of at least 400°C, at least 500°C, at least 600°C, or at least 650°C. The second calcination step may be carried out at a temperature of 1000°C or less, 900°C or less, 800°C or less, or 750°C or less. The material to be calcined may be maintained at a temperature of 400°C, at least 500°C, at least 600°C, or at least 650°C for a period of at least 30 minutes, at least 1 hour, or at least 2 hours. The time period may be less than 24 hours. The second calcination step may be shorter than the first calcination step.

[0192] The second calcination step may be carried out under a CO2-free atmosphere as described above with reference to the first calcination step.

[0193] The method may include one or more milling steps, which may be performed after the first and / or second calcining step. The nature of the milling equipment is not particularly limited. For example, it may be a ball mill, a planetary ball mill or a roller bed mill. Milling may be performed until the particles (e.g., secondary particles) reach a desired particle size. For example, particles (e.g., secondary particles) of lithium nickel oxide are typically milled until they have a D50 particle size of at least 5 μm, e.g., at least 5.5 μm, at least 6 μm, or at least 6.5 μm. Particles (e.g., secondary particles) of lithium nickel oxide are typically milled until they have a D50 particle size of 15 μm or less, e.g., 14 μm or less or 13 μm or less.

[0194] The method of the present invention may further include the step of forming an electrode (usually a cathode) comprising a lithium nickel oxide material. Typically, this is performed by the following steps: forming a slurry of particulate lithium nickel oxide, applying the slurry to the surface of a current collector (e.g., an aluminum current collector) and optionally processing (e.g., calendering) to increase the density of the electrode. The slurry may include one or more of a solvent, a binder, a carbon material, and other additives.

[0195] Typically, the electrodes of the present invention will have a surface area of ​​at least 2.5 g / cm 3 , at least 2.8g / cm 3 or at least 3g / cm 3 The electrode density can be 4.5g / cm 3 or less, or 4g / cm 3 or less. The electrode density is the electrode density (mass / volume) of the electrode, excluding the current collector on which the electrode is formed. Therefore, it includes the contribution from the active material, any additives, any additional carbon material, and any remaining binder.

[0196] The method of the present invention may further comprise constructing a battery or electrochemical cell comprising an electrode comprising lithium nickel oxide. The battery or cell typically also comprises an anode and an electrolyte. The battery or cell typically may be a secondary (rechargeable) lithium (e.g., lithium ion) battery.

[0197] The present invention will now be described with reference to the following examples, which are provided to aid understanding of the present invention and are not intended to limit the scope of the present invention.

[0198] Example

[0199] Comparative Example 1 - Preparation of Matrix Material

[0200] Comparative Example 1A - Matrix 1 (Li 1.030 Ni 0.953 Co 0.030 Mg 0.010 O2)

[0201] 100g Ni 0.960 Co 0.031 Mg 0.099 (OH)2 and 26.36 g LiOH were dry mixed in a polypropylene bottle for 30 minutes. LiOH was pre-dried under vacuum at 200°C for 24 hours and kept dry in a purged glove box filled with dry N2.

[0202] The powder mixture was charged into a 99%+ alumina crucible and calcined under an artificial air mixture without CO2, the air mixture being 80:20 N2:O2. Calcination was performed as follows: reaching 450°C (5°C / min) for 2 hours, ramping to 700°C (2°C / min) for 6 hours, and naturally cooling to 130°C. During the entire calcination and cooling process, the artificial air mixture was flowed through the powder bed. The title compound was thus obtained.

[0203] The sample was then removed from the 130 °C furnace and transferred to a high alumina lined grinding jar and ground on a roller bed mill until D 50 Between 12.0 μm and 12.5 μm.

[0204] D 50 The particle size was measured using a Malvern Mastersizer 3000 under Mie scattering approximation according to 2017 ASTM B822 and found to be 9.5 μm. The chemical formula of the material was determined by ICP analysis to be Li 1.030 Ni 0.953 Co 0.030 Mg 0.010 O2.

[0205] Comparative Example 1B - Matrix 2 (Li 1.019 Ni0.949 Co 0.031 Mg 0.020 O2)

[0206] The procedure according to Comparative Example 1A was repeated except that 26.21 g of LiOH was mixed with 100 g of Ni 0.948 Co 0.031 Mg 0.021 (OH)2 were dry mixed together. Thus, the title compound was obtained. 50 The chemical formula of the material was determined by ICP analysis to be Li 1.019 Ni 0.949 Co 0.031 Mg 0.020 O2.

[0207] Comparative Example 1C - Matrix 3 (Li 1.027 Ni 0.923 Co 0.049 Mg 0.029 O2)

[0208] The procedure according to Comparative Example 1A was repeated except that 24.8 g of LiOH was mixed with 100 g of Ni 0.917 Co 0.050 Mg 0.033 (OH)2 were dry mixed together. Thus, the title compound was obtained. 50 The chemical formula of the material was determined by ICP analysis to be Li 1.027 Ni 0.923 Co 0.049 Mg 0.029 O2.

[0209] Comparative Example 1D - Matrix 4 (Li 1.007 Ni 0.923 Co 0.049 Mg 0.038 O2)

[0210] The procedure according to Comparative Example 1A was repeated except that 25.92 g of LiOH was mixed with 100 g of Ni 0.915 Co 0.049 Mg 0.036 (OH)2 were dry mixed together. Thus, the title compound was obtained. 50 The chemical formula of the material was determined by ICP analysis to be Li 1.007 Ni 0.923 Co 0.049 Mg 0.038 O2.

[0211] Comparative Example 1E - Matrix 5 (Li 0.998 Ni 0.917Co 0.049 Mg 0.052 O2)

[0212] The procedure according to Comparative Example 1A was repeated except that 25.75 g of LiOH was mixed with 100 g of Ni 0.903 Co 0.048 Mg 0.049 (OH)2 were dry mixed together. Thus, the title compound was obtained. The chemical formula of the material was determined by ICP analysis to be Li 0.998 Ni 0.917 Co 0.049 Mg 0.052 O2.

[0213] Comparative Example 1F - Matrix 6 (Li 1.024 Ni 0.926 Co 0.045 Mg 0.037 O2)

[0214] The procedure according to Comparative Example 1A was repeated except that 25.94 g of LiOH was mixed with 100 g of Ni 0.918 Co 0.045 Mg 0.037 (OH)2 were dry mixed together. Thus, the title compound was obtained. 50 The chemical formula of the material was determined by ICP analysis to be Li 1.024 Ni 0.926 Co 0.045 Mg 0.037 O2.

[0215] Comparative Example 1G - Matrix 7 (Li 1.003 Ni 0.956 Co 0.030 Mg 0.020 O2)

[0216] The procedure according to Comparative Example 1A was repeated except that 26.20 g of LiOH was mixed with 100 g of Ni 0.952 Co 0.029 Mg 0.019 (OH)2 were dry mixed together. Thus, the title compound was obtained. 50 The chemical formula of the material was determined by ICP analysis to be Li 1.003 Ni 0.956 Co 0.030 Mg 0.020 O2.

[0217] Comparative Example 1H - Matrix 8 (Li 1.009 Ni 0.957 Co 0.030 Mg 0.015 O2)

[0218] The procedure according to Comparative Example 1A was repeated except that 26.29 g of LiOH was mixed with 100 g of Ni 0.957 Co 0.029 Mg 0.014 (OH)2 were dry mixed together. Thus, the title compound was obtained. 50 The chemical formula of the material was determined by ICP analysis to be Li 1.009 Ni 0.957 Co 0.030 Mg 0.015 O2.

[0219] Comparative Example 1J - Matrix 9 (Li 1.005 Ni 0.944 Co 0.029 Mg 0.038 O2)

[0220] The procedure according to Comparative Example 1A was repeated except that 25.96 g of LiOH was mixed with 100 g of Ni 0.935 Co 0.029 Mg 0.037 (OH)2 were dry mixed together. Thus, the title compound was obtained. 50 The chemical formula of the material was determined by ICP analysis to be Li 1.005 Ni 0.944 Co 0.029 Mg 0.038 O2.

[0221] Comparative Example 1K - Matrix 10 (Li 0.996 Ni 0.914 Co 0.053 Mg 0.051 O2)

[0222] The procedure according to Comparative Example 1A was repeated except that 25.75 g of LiOH was mixed with 100 g of Ni 0.900 Co 0.053 Mg 0.048 (OH)2 were dry mixed together. Thus, the title compound was obtained. 50 The chemical formula of the material was determined by ICP analysis to be Li 0.996 Ni 0.914 Co 0.053 Mg 0.051 O2.

[0223] Substrates 12 to 20 listed in Table 3 below were prepared by a similar method as Substrates 1 to 10.

[0224] Example 1 - Preparation of surface modified materials

[0225] Example 1A - Compound 1 (Li 1.018 Ni 0.930 Co 0.049 Mg 0.010 Al 0.006 O2)

[0226] The product of Comparative Example 1A was sieved through a 53 μm sieve and transferred to a N2 purged glove box. An aqueous solution containing 5.91 g Co(NO3)2.6H2O, 0.47 g LiNO3 and 2.44 g Al(NO3)3.9H2O in 100 mL of water was heated to between 60°C and 65°C. 100 g of the sieved powder was quickly added while stirring vigorously. The slurry was stirred at a temperature between 60°C and 65°C until the supernatant was colorless. The slurry was then spray dried.

[0227] After spray drying, the powder was loaded into a 99%+ alumina crucible and calcined under an artificial air mixture without CO2, the air mixture being 80:20 N2:O2. Calcination was performed as follows: temperature was raised to 130°C (5°C / min) for 5.5 hours, temperature was raised to 450°C (5°C / min) for 1 hour, temperature was raised to 700°C (2°C / min) for 2 hours, and naturally cooled to 130°C. During the entire calcination and cooling process, the artificial air mixture was flowed through the powder bed. The title compound was thus obtained.

[0228] The sample was then removed from the 130°C oven and transferred to a purged N2-filled glove box.

[0229] The samples were ground in a high alumina lined grinding jar on a roller bed mill. The target endpoint of the grinding was when D 50 Between 10 μm and 11 μm; D was measured after grinding 50 , and was found to be 9.5 μm. The sample was passed through a 53 μm sieve and stored in a purged glove box filled with N2. The water content of the material was 0.18 wt%. The chemical formula of the material was determined by ICP analysis to be Li 1.018 Ni 0.930 Co 0.049 Mg 0.010 Al 0.006 O2.

[0230] Example 1B - Compound 2 (Li 1.002 Ni 0.927 Co 0.053 Mg 0.020 Al 0.0065 O2)

[0231] The product of Comparative Example 1B was subjected to the procedure described in Example 1A, except that the aqueous solution contained 5.90 g Co(NO3)2.6H2O, 0.47 g LiNO3 and 2.43 g Al(NO3)3.9H2O in 100 mL water. The title compound was obtained. 50 The material has a water content of 0.28 wt %. The chemical formula of the material was determined by ICP analysis to be Li 1.002 Ni 0.927 Co 0.053 Mg 0.020 Al 0.0065 O2.

[0232] Example 1C - Compound 3 (Li 0.995 Ni 0.909 Co 0.068 Mg 0.027 Al 0.0065 O2)

[0233] The product of Comparative Example 1C was subjected to the procedure described in Example 1A, except that the aqueous solution contained 5.89 g Co(NO3)2.6H2O, 0.46 g LiNO3 and 2.43 g Al(NO3)3.9H2O in 100 mL water. The title compound was obtained. 50 The material has a water content of 0.2 wt %. The chemical formula of the material was determined by ICP analysis to be Li 0.995 Ni 0.909 Co 0.068 Mg 0.027 Al 0.0065 O2.

[0234] Example 1D - Compound 4 (Li 0.985 Ni 0.913 Co 0.061 Mg 0.037 Al 0.0069 O2)

[0235] The product of Comparative Example 1D was subjected to the procedure described in Example 1A, except that the aqueous solution contained 3.94 g Co(NO3)2.6H2O and 2.43 g Al(NO3)3.9H2O in 100 mL water, but did not contain any LiNO3. The title compound was obtained. 50 The material has a water content of 0.26 wt %. The chemical formula of the material was determined by ICP analysis to be Li 0.985 Ni 0.913 Co 0.061 Mg 0.037 Al 0.0069 O2.

[0236] Example 1E - Compound 5 (Li 0.980 Ni 0.905 Co 0.061 Mg 0.051 Al 0.0065 O2)

[0237] The product of Comparative Example 1E was subjected to the procedure described in Example 1A, except that the aqueous solution contained 3.93 g Co(NO3)2.6H2O and 2.42 g Al(NO3)3.9H2O in 100 mL water, but did not contain any LiNO3. The title compound was obtained. 50 The material has a water content of 0.09 wt %. The chemical formula of the material was determined by ICP analysis to be Li 0.980 Ni 0.905 Co 0.061 Mg 0.051 Al 0.0065 O2.

[0238] Example 1F - Compound 6 (Li 1.003 Ni 0.923 Co 0.045 Mg 0.038 Al 0.0062 O2)

[0239] The product of Comparative Example 1F was subjected to the procedure described in Example 1A, except that the aqueous solution contained 2.43 g of Al(NO3)3.9H2O in 100 mL of water, but did not contain any Co(NO3)2.6H2O or LiNO3. The title compound was obtained. 50 The result was 7.5 μm. The water content of the material was 0.18 wt %. The chemical formula of the material was determined by ICP analysis to be Li 1.003 Ni 0.92 3Co 0.045 Mg 0.038 Al 0.0062 O2.

[0240] Example 1G - Compound 7 (Li 0.997 Ni 0.952 Co 0.029 Mg 0.019 Al 0.0065 O2)

[0241] The product of Comparative Example 1G was subjected to the procedure described in Example 1A, except that the aqueous solution contained 2.44 g of Al(NO3)3.9H2O in 100 mL of water, but did not contain any Co(NO3)2.6H2O or LiNO3. The title compound was obtained. 50The material has a water content of 0.29 wt%. The chemical formula of the material was determined by ICP analysis to be Li 0.997 Ni 0.952 Co 0.029 Mg 0.019 Al 0.0065 O2.

[0242] Example 1H - Compound 8 (Li 1.002 Ni 0.919 Co 0.064 Mg 0.014 Al 0.0062 O2)

[0243] The product of Comparative Example 1H was subjected to the procedure described in Example 1A, except that the aqueous solution contained 11.82 g Co(NO3)2.6H2O, 1.88 g LiNO3 and 2.44 g Al(NO3)3.9H2O in 100 mL water. The title compound was obtained. 50 The material has a water content of 0.29 wt %. The chemical formula of the material was determined by ICP analysis to be Li 1.002 Ni 0.919 Co 0.064 Mg 0.014 Al 0.0062 O2.

[0244] Example 1J - Compound 9 (Li 0.980 Ni 0.909 Co 0.066 Mg 0.037 Al 0.0066 O2)

[0245] The product of Comparative Example 1J was subjected to the procedure described in Example 1A, except that the aqueous solution contained 11.77 g Co(NO3)2.6H2O, 1.87 g LiNO3 and 2.44 g Al(NO3)3.9H2O in 100 mL water. The title compound was obtained. 50 The material has a water content of 0.08 wt %. The chemical formula of the material was determined by ICP analysis to be Li 0.980 Ni 0.909 Co 0.066 Mg 0.037 Al 0.0066 O2.

[0246] Example 1K - Compound 10 (Li 0.987 Ni 0.900 Co 0.064 Mg 0.051 Al 0.0065 O2)

[0247] The product of Comparative Example 1K was subjected to the procedure described in Example 1A, except that the aqueous solution contained 3.93 g Co(NO3)2.6H2O and 2.42 g Al(NO3)3.9H2O in 100 mL water, but did not contain any LiNO3. The title compound was obtained. 50 The material has a water content of 0.17 wt %. The chemical formula of the material was determined by ICP analysis to be Li 0.98 7Ni 0.900 Co 0.064 Mg 0.051 Al 0.0065 O2.

[0248] Example 1L - Compound 11 (Li 0.984 Ni 0.877 Co 0.115 Mg 0.010 Al 0.0066 O2)

[0249] 100g Ni 0.905 Co 0.084 Mg 0.010 (OH)2 and 26.33 g LiOH were dry mixed in a polypropylene bottle for 1 hour. LiOH was predried under vacuum at 200°C for 24 hours and kept dry in a glove box purged with dry N2.

[0250] The powder mixture was charged into a 99%+ alumina crucible and calcined under an artificial air mixture without CO2, the air mixture being 80:20 N2:O2. Calcination was performed as follows: reaching 450°C (5°C / min) for 2 hours, ramping to 700°C (2°C / min) for 6 hours, and naturally cooling to 130°C. The artificial air mixture was flowed through the powder bed throughout the calcination and cooling process.

[0251] The sample was then removed from the 130°C furnace and transferred to a purged glove box filled with N2. The sample was transferred to a high alumina lined grinding jar and ground on a roller bed mill until D 50 Between 12.0–12.5 μm.

[0252] After grinding, the product was sieved through a 53 μm sieve and transferred to a purged glove box filled with N2. An aqueous solution containing 11.83 g Co(NO3)2.6H2O, 1.88 g LiNO3 and 2.44 g Al(NO3)3.9H2O in 100 mL of water was heated to between 60°C and 65°C. 100 g of the sieved powder was quickly added while stirring vigorously. The slurry was stirred at a temperature between 60°C and 65°C until the supernatant was colorless. The slurry was then spray dried.

[0253] After spray drying, the powder was loaded into a 99%+ alumina crucible and calcined under an artificial air mixture without CO2, the air mixture being 80:20 N2:O2. Calcination was performed as follows: temperature was raised to 130°C (5°C / min) for 5.5 hours, temperature was raised to 450°C (5°C / min) for 1 hour, temperature was raised to 700°C (2°C / min) for 2 hours, and naturally cooled to 130°C. During the entire calcination and cooling process, the artificial air mixture was flowed through the powder bed. The title compound was thus obtained.

[0254] The sample was then removed from the 130 °C oven and transferred into a glove box filled with N2.

[0255] The samples were ground in a high alumina lined grinding jar on a roller bed mill. The end point of grinding was when D50 was between 10 μm and 11 μm; D 50 , and found to be 8.8 μm. The sample was passed through a 53 μm sieve and stored in a purged glove box filled with N2.

[0256] The water content of the material was 0.4 wt%. The chemical formula of the material was determined by ICP analysis to be Li 0.984 Ni 0.877 Co 0.11 5Mg 0.010 Al 0.0066 O2.

[0257] Compounds 12 to 20 (listed in Table 3 below) were prepared by methods similar to those of compounds 1 to 10 using the following substrates:

[0258] Table 1

[0259] Compound Matrix Compound 12 Base 12 Compound 13 Base 13 Compound 14 Base 14 Compound 15 Base 15 Compound 16 Base 16 Compound 17a Base 17 Compound 17b Base 17 Compound 18a Base 18 Compound 18b Base 18 Compound 19 Base 19 Compound 20 Base 20

[0260] Li2CO3 content

[0261] The surface Li2CO3 content in the samples was determined by a two-stage titration using phenolphthalein and bromophenol blue. For the titration, surface lithium carbonate was extracted from a sample of each material by stirring in deionized water for 5 minutes to obtain an extract solution, which was separated from the residual solids. A phenolphthalein indicator was added to the extract solution, and the extracted solution was titrated with an HCl solution until the extract solution became clear (this indicates that all LiOH has been removed). A bromophenol blue indicator was added to the extract solution, and the extracted solution was titrated with an HCl solution until the extract solution turned yellow. The amount of lithium carbonate in the extract solution was calculated from the bromophenol titration step, assuming that 100% of the surface lithium carbonate was extracted into the extract solution, and the weight % of the surface lithium carbonate in each sample was calculated.

[0262] The results of the test materials are shown in Table 2:

[0263] Table 2

[0264]

[0265] Composition analysis

[0266] The total magnesium and cobalt contents (wt % based on total particle weight) in the comparative and inventive materials were determined by ICP and are given in Table 3 below.

[0267] The surface cobalt content was calculated by subtracting the ICP Co wt% in the matrix material from the ICP Co wt% in the final material. The core cobalt content was taken as the ICP Co wt% in the matrix material.

[0268] ICP (Inductively Coupled Plasma)

[0269] The elemental composition of the compounds was measured by ICP-OES. To this end, 0.1 g of material was digested with aqua regia (hydrochloric acid and nitric acid in a ratio of 3:1) at about 130°C and made up to 100 mL. ICP-OES analysis was performed on an Agilent 5110 using matrix-matched calibration standards and yttrium as an internal standard. The lines and calibration standards used were those recommended by the instrument.

[0270] Electrochemical testing

[0271] The electrodes were prepared with a 94:3:3 active:carbon:binder formulation and an ink with a solids content of 65%. 0.6 g SuperC65 carbon was mixed with 5.25 g N-methylpyrrolidone (NMP) on a mixer. 18.80 g active material was added and used The mixer was further mixed. Finally, 6.00 g 5130 binder solution (10 wt% in NMP) and mixed in a Thinky mixer. The resulting ink was cast onto aluminum foil using a 125 μm fixed blade coater and dried at 120° C. for 60 minutes. After drying, the electrode sheet was calendered in an MTI calender to achieve 3 g / cm 3 The individual electrodes were cut and dried under vacuum overnight before being transferred to an argon-filled glove box.

[0272] Coin cells were constructed using a lithium anode and 1M LiPF6 in a 1:1:1 EC (ethylene carbonate):EMC (ethyl methyl carbonate):DMC (dimethyl carbonate) + 1 wt% VC (vinylene carbonate) electrolyte. The loading of the selected electrode was 9.0 mg / cm 2, and the density is 3g / cm 3 The electrochemical measurements were taken as the average of three cells measured at 23 °C in a voltage window of 3.0–4.3 V.

[0273] The electrochemical characteristics evaluated included first cycle efficiency (FCE), 0.1C specific capacity, 1.0C specific capacity, capacity retention, and DCIR increase using a 10 s pulse.

[0274] The capacity retention and DCIR increase were determined based on the performance after 50 cycles at 1C.

[0275] Table 3 below includes details of the materials tested.

[0276]

[0277]

[0278]

[0279] Experimental design

[0280] Traditionally, experiments are planned to vary one factor at a time while holding the other factors constant. An alternative approach is "experimental design" in which multiple variables are varied at once, allowing a large experimental space to be covered using relatively few experimental points. Computer-based statistical analysis is then applied to identify key interactions.

[0281] The compounds prepared in the above examples were prepared and analyzed according to the experimental method design.Statistical analysis determined the following correlations and p values ​​(p value indicates the statistical significance of the result, and p value < 0.05 indicates a statistically significant result), as shown in Table 4 below.

[0282] Table 4

[0283]

[0284] This suggests that the Mg content and the Co content in the core have a negative impact on the capacity, with the effect of Mg being stronger. However, the effect of the Co content in the surface layer on the capacity is not statistically significant.

[0285] In contrast, the Mg content in the core, the Co content, and subsequently the Co content in the surface all have a positive impact on the capacity retention. Interestingly, the Co content in the shell has a greater impact on the capacity retention than the content in the core. Combined with the observation that the Co content in the surface layer does not have a statistically significant effect on reducing the capacity, shifting the Co content from the core to the surface layer of the material provides a strategy to improve the capacity retention while maintaining excellent capacity.

Claims

1. A surface-modified particulate lithium nickel oxide material comprising particles having formula I Li a Ni x Co y Mg z Al p M q O 2+b Formula I in: 0.8≤a≤1.2 0.8≤x<1 0.010≤y≤0.12 0.007≤z≤0.030 0≤p≤0.01 0≤q≤0.2; and -0.2≤b≤0.2; wherein M is selected from the group consisting of Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, W, Mo, Ta, Y, Sc, Nb, Pb, Ru, Rh and Zn and combinations thereof; and wherein the particle comprises a core and an enriched surface layer at a surface of the core, and wherein the enriched surface layer comprises 0.8 wt % or more of cobalt based on the total weight of the particle.

2. The particulate lithium nickel oxide material of claim 1, wherein the surface enrichment layer comprises 1 wt% or more cobalt based on the total weight of the particle.

3. A particulate lithium nickel oxide material according to any one of the preceding claims, wherein y≤0.10 and / or wherein 0.012≤z.

4. The particulate lithium nickel oxide material of any one of the preceding claims, wherein y≤0.093, y≤0.090 or y≤0.

085.

5. A particulate lithium nickel oxide material according to any one of the preceding claims, wherein (i) 0.055≤y or 0.060≤y and / or (ii) 0.022≤z.

6. A particulate lithium nickel oxide material according to any one of the preceding claims, wherein 0.018 ≤ z.

7. A particulate lithium nickel oxide material according to any preceding claim having a D50 particle size in the range 4 to 20 μm, for example 5 to 15 μm.

8. A particulate lithium nickel oxide material according to any one of the preceding claims, wherein the c-axis contraction during the H2→H3 phase transition within the material is less than 3.9% as measured by ex situ XRPD.

9. A particulate lithium nickel oxide material according to any one of the preceding claims, wherein at 9.0 mg / cm 2 The electrode loading is 3.0 g / cm3 At an electrode density of 1000 nm, the capacity retention rate of the granular lithium nickel oxide material after 50 cycles tested in a battery is at least 93%, and / or For example, at 23°C and 1C charge / discharge rate, at 9.0 mg / cm 2 The electrode loading is 3.0 g / cm 3 At an electrode density of 1000 nm, the granular lithium nickel oxide material has a DCIR increase percentage of less than 50% after 40 cycles tested in a battery, and / or For example, at 23°C and 1C charge / discharge rate, at 9.0 mg / cm 2 The electrode loading is 3.0 g / cm 3 At an electrode density of , the specific capacity of the granular lithium nickel oxide material is at least 160 mAh / g when tested in a battery.

10. A method for preparing a granular lithium nickel oxide material having formula I Li a Ni x Co y Mg z Al p M q O 2+b Formula I in: 0.8≤a≤1.2 0.8≤x<1 0.010≤y≤0.12 0.010≤z≤0.030 0≤p≤0.01 0≤q≤0.2; and -0.2≤b≤0.2; wherein M is selected from the group consisting of Mn, V, Ti, B, Zr, Sr, Ca, Cu, Sn, Cr, Fe, Ga, Si, W, Mo, Ta, Y, Sc, Nb, Pb, Ru, Rh and Zn and combinations thereof; and The method comprises the following steps: mixing a lithium-containing compound with a nickel-containing compound, a cobalt-containing compound, a magnesium-containing compound, and optionally an M-containing compound and / or an aluminum-containing compound to obtain a mixture, wherein a single compound may optionally contain two or more of Ni, Co, Mg, Al and M; calcining the mixture to obtain a calcined material; and The first calcined material is contacted with a cobalt-containing compound and optionally one or more of an aluminum-containing compound, a lithium-containing compound, and an M-containing compound in a surface modification step to form an enriched surface layer on the first calcined material, such that the enriched surface layer contains 0.8 wt% or more of cobalt based on the total weight of the particle.

11. A cathode comprising the particulate lithium nickel oxide material according to any one of claims 1 to 9.

12. A lithium secondary cell or battery comprising the cathode according to claim 11.

13. Use of the particulate lithium nickel oxide according to any one of claims 1 to 9 for improving the capacity retention of a lithium secondary battery or battery pack.

Citation Information

Patent Citations

  • Gradient cathode material for lithium rechargeable batteries

    US6921609B2